Efecto de la inclusión de harina de Moringa oleífera en parámetros productivos y de salud de pollos COBB 500 - Cuadros Zambrano, Evelyn Nayeli (2024)
The purpose of this research was to include (Moringa oleifera) flour in the production and health parameters of COBB 500 chickens. 200 experimental units distributed in 20 replicates were used, which were randomly distributed in 3 treatments (1%, 2%, 3%) and a control, and comparisons of means were made in the variables of productive, health and cost-benefit parameters, using the Tukey technique at 5%. The results were analyzed using the statistical software InfoStad (2020) and Microsoft Excel (2022). In addition, descriptive statistics of the variables, measures of central tendency (mean) and dispersion (coefficient of variation, deviation and standard error of the mean) were performed. A highly significant difference was obtained (p<0.01) both in: productive parameters, lymphoid organs, additionally the cost-benefit relation was performed (p<0.01) having as an answer that the group fed with 1% of flour inclusion presents better economic profitability. It is concluded that moringa flour has positive effects on productive parameters, such as weight gain, feed conversion and carcass yield in broilers.